2021
DOI: 10.1186/s12889-021-10699-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary patterns and anaemia in 6- to 23-month-old infants in central South China

Abstract: Background Anaemia is prevalent in children. Therefore, this study examined the association between dietary patterns and anaemia among children in central South China. Methods Cross-sectional studies were conducted in Mayang, central South China, in 2015 and 2018. Diet data were collected using a questionnaire, and dietary patterns were identified via exploratory factor analysis. Haemoglobin was measured to assess anaemia status. Associations betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
4
6
0
Order By: Relevance
“…Similar to research in other LMICs, several studies have found high rates of child undernutrition in rural China [ 23 , 24 ]. In China, a middle-income country, there is a large and substantial number of undernourished children who live in rural areas.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar to research in other LMICs, several studies have found high rates of child undernutrition in rural China [ 23 , 24 ]. In China, a middle-income country, there is a large and substantial number of undernourished children who live in rural areas.…”
Section: Introductionsupporting
confidence: 70%
“…Specifically, the findings indicate that Han caregivers typically have higher adherence to MNP than do minority groups, such as the Yi and Tibetan [ 32 – 34 ]. In rural Western China, ethnic groups have distinct food cultures and feeding practices, in addition to different lifestyles [ 24 , 28 , 35 ], that may influence how caregivers access MNP and how they feed MNP to their children. To the best of our knowledge, no study has examined the association between MNP implementation success/failure and the delivery patterns and feeding behaviors of MNP across different ethnic groups in China.…”
Section: Introductionmentioning
confidence: 99%
“…Anemia prevalence in 0–18-year-old children from China in national [ 30 , 31 , 47 ] and subnational studies (mostly covering the western region) ranged from 2.7 to 86%, and ID prevalence ranged from 7.3% to 62% [ 50 , 52 , 55 , 56 , 57 , 60 , 61 , 64 , 65 , 67 , 68 , 75 , 87 , 95 , 97 , 102 , 103 , 105 ]. The prevalence of anemia in children decreased with age ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The beverage and snack pattern is characterized by high intakes of beverages and snacks, which may increase metabolic risk (e.g., obesity [ 44 ]). Our previous studies reported that the dietary pattern represents the overall diet intake [ 45 , 46 ]. These results implied that plasma DHA may become a biomarker to evaluate the recent quality of comprehensive diet intake.…”
Section: Discussionmentioning
confidence: 99%